Penerapan Kombinasi Metode Multi-Attribute Utility Theory (MAUT) dan Rank Sum Dalam Pemilihan Siswa Terbaik - Saputra, Williyandi; Wardana, Suwarman Adi; Wahyuda, Hana; Megawaty, Dyah Ayu (PT. Tech Cart Press, 2024)
The selection of the best students can involve a variety of issues that need to be considered. Some of the problems that arise in the process of selecting the best students include the determination of clear and objective criteria to select the best students, the availability of accurate data and information to assess student achievement and qualifications, and uncertainty or controversy related to the decisions taken. This study aims to apply a combination of Multi-Attribute Utility Theory (MAUT) and Rank Sum methods in selecting the best students so as to make it easier for schools, especially the student affairs department, to determine the best students at the end of each semester. The ranking results showed that rank 1 was obtained with a final grade of 0.5327 on behalf of student Nadia Kadhita Andriane, rank 2 was obtained with a final grade of 0.5327 on behalf of student Fio Abiyu Yahara, and rank 3 was obtained with a final grade of 0.5300 on behalf of student Robinson Pasaribu.